2019
DOI: 10.21511/imfi.16(4).2019.08
|View full text |Cite
|
Sign up to set email alerts
|

Capital structure construct: a new approach to behavioral finance

Abstract: Within the framework of behavioral finance, this research shows that financial behavior can be assessed as a cognitive construct. Using certain variables, a multidimensional "cognitive finance" construct can thus be established. Through a technological -psychometric type design with descriptive data analysis, a factor analysis is presented to determine which latent variables tend to charge significantly in order to assess the validity of the dimensions comprising the construct of capital structure and explore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Behavioral finance is still among the interesting areas to explore (Xing, 2020). Reyes et al (2019) found that financial behavior can be studied as a cognitive structure. Thus, a multidimensional "financial-cognitive" structure can be created using specific variables.…”
Section: Capital Structure Legal Environment Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Behavioral finance is still among the interesting areas to explore (Xing, 2020). Reyes et al (2019) found that financial behavior can be studied as a cognitive structure. Thus, a multidimensional "financial-cognitive" structure can be created using specific variables.…”
Section: Capital Structure Legal Environment Theorymentioning
confidence: 99%
“…Thus, a multidimensional "financial-cognitive" structure can be created using specific variables. Their model explained how decision-makers reacted in the face of environmental conditions and uncertainty and found that they directly impacted the loss of revenue assessment of the firm (Reyes et al, 2019). Jurevičienė et al (2014) found that behavioral financial affairs are significant at both corporate and individual levels.…”
Section: Capital Structure Legal Environment Theorymentioning
confidence: 99%